The Influence Of Realization Of Provincial Financial Assistance Transfer On Participation Recipients Of Contribution Assistance- West Java Health Insurance - Rabbani, Kireyna Fridola; Hastuti, Hastuti (Indonesian Accounting Research Journal, 2025)
Fiscal decentralization can be the answer to the problem of low quality of life of the people in Indonesia. One of the effective implementations of fiscal decentralization is the synergy and harmonization of central and regional spending in the form of Transfers to Regions. Transfers to Regions focus on mandatory spending, one of which is in the health sector. The government's efforts to equalize the rights to health services are to use Financial Assistance Spending transfer funds sourced from the State Budget (APBN). This study aims to assess the effect of the effectiveness of provincial financial assistance spending on National Health Insurance (JKN) Contribution Assistance Recipient Participants (PBI). The population in this study was 27 regencies/cities in West Java Province. The analysis was using logistic regression to test the effect and predict the probability of occurrence of dependent variables that can be predicted by independent variables with the help of the SPSS 26 application. The results of the study showed that provincial financial assistance transfer spending had a significant effect on the PBI APBD segment but was not significant for the PBI APBN segment.